Androgen- and estrogen-receptor mediated activities of 4-hydroxytestosterone, 4-hydroxyandrostenedione and their human metabolites in yeast based assays. (August 2018) - Keiler, Annekathrin Martina; Zierau, Oliver; Wolf, Sylvi; Diel, Patrick; Schänzer, Wilhelm; Vollmer, Günter; Machalz, David; Wolber, Gerhard; Parr, Maria Kristina
Highlights: Formestane, 4-HOT and metabolites were tested in yeast androgen and estrogen screen. Androgenic effects were observed for all tested compounds, except for one. Androgen receptor and estrogen receptor binding was modeled in silico. Abuse might be traced in urine samples using the yeast androgen screen. Abstract: 4-Hydroxyandrost-4-ene-3, 17-dione, also named formestane, is an irreversible aromatase inhibitor and therapeutically used as anti-breast cancer medication in post-menopausal women. Currently, no therapeutical indication led to approval of its 17-hydroxylated analog 4-hydroxytestosterone, an anabolic steroid. However, it is currently investigated in a clinical trial for breast cancer. In context with sports doping, aromatase inhibitors are administered to reduce estrogenic side effects of misused anabolic substances or their metabolites. Therefore, both substances are prohibited in sports by the World Anti-Doping Agency (WADA). Analysis of urinary phase I and phase II metabolites showed similar results for both compounds. In the current investigation, 4-hydroxyandrost-4-ene-3, 17-dione, 4-hydroxytestosterone and seven of their described urinary metabolites as well as 2α-hydroxyandrostenedione were tested in the yeast androgen screen and the yeast estrogen screen. Androgenic effects were observed for all tested substances, except for one, which showed anti-androgenic properties. With regard to the yeast estrogen screen, estrogenic effects were observed for only two metabolites at rather high concentrations, while six out of the ten substances tested showed anti-estrogenic properties. In terms of the strong androgenic effect observed for 4-hydroxytestosterone (10 −8  M), 4-hydroxyandrost-4-ene-3, 17-dione (10 −8  M) and two more urinary metabolites, the yeast androgen assay may also be used to trace abuse in urine samples.